The factors contributing to the success of community learning centers program in rural community literacy development in the Islamic Republic of Iran: case studies of two rural communities - Zolfaghari, Akbar; Sabran, Mohammad Shatar; Zolfaghari, Azam (Canadian Center of Science and Education, 2009)
Literacy plays a significant role in community development. Without literacy, development goals cannot be achieved easily. Through literacy, the community does not face any challenge to improve their quality of life. For this reason, developed and developing countries nowadays are investing a lot on social and natural innovations, plus human capital in communities to increase their level of literacy. Iran is no exception. For this purpose, the government of Iran has formulated several community literacy development programs in the country. One of the major programs that has been implemented for this purpose is the Community Learning Centers Program (CLCP) (Mehdizadeh, 2003).In the Islamic Republic of Iran, CLCP was implemented in early 2000. It has had very encouraging results in solvingthe problem of illiteracy in this country. All communities that have pioneered the program have experienced a remarkable increase in their literacy level (Ebrahimian, Bahirai, & Iranian National Commission for ISESCO, 2006). What are the reasons of such achievements? Therefore, the main purpose of this study is to investigate the factors thathave contributed to the success of CLCP in community literacy development in the Islamic republic of Iran.